2007
DOI: 10.1007/s11062-008-9003-x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of nociceptive signalling and mechanisms underlying its modulation

Abstract: Specific features of calcium signalling in neurons of the nociceptive system, in particular in primary afferent (dorsal root ganglion) and secondary dorsal horn spinal units, are described. The roles of different types of calcium channels and intracellular Ca stores (those of the mitochondria and endoplasmic reticulum) and interactions between these cellular structures in the norm and under pathological conditions (in particular in diabetic neuropathy) are discussed.It is well known that calcium signalling pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Nociceptive afferent fibers are processes of afferent neurons with a relatively small diameter of the somata (small-and mid-sized neurons of the sensory ganglia); in other words, the size of the soma of such neurons and their belonging to the system of nociception demonstrate rather close correlation. This peculiarity has been mentioned in numerous publications; its description in a few papers [1][2][3] was close to the topic of our review.…”
Section: General Characteristics Of the System Of Nociceptionsupporting
confidence: 67%
See 2 more Smart Citations
“…Nociceptive afferent fibers are processes of afferent neurons with a relatively small diameter of the somata (small-and mid-sized neurons of the sensory ganglia); in other words, the size of the soma of such neurons and their belonging to the system of nociception demonstrate rather close correlation. This peculiarity has been mentioned in numerous publications; its description in a few papers [1][2][3] was close to the topic of our review.…”
Section: General Characteristics Of the System Of Nociceptionsupporting
confidence: 67%
“…Calcium currents through the membrane of nociceptive primary afferent neurons are due to the existence of voltage-dependent calcium channels of types L, T, N, R, and P/Q [1,2]. The activation of high-threshold N-type calcium channels is closely related to generation of nociceptive signals; it was found that these N-type channels are sensitive to changes in the temperature.…”
Section: Ion Channels In the Plasma Membranes Of Nociceptive Neuronsmentioning
confidence: 99%
See 1 more Smart Citation